2011
DOI: 10.1097/scs.0b013e31820779d5
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Location of Facial Nerve Deep to Parotid Gland

Abstract: The knowledge of normal and variant anatomy of the facial nerve is essential for safe surgery of the parotid gland. The location of a parotid mass in relation to the course of the facial nerve determines whether superficial or total parotidectomies should be performed. The variant course of the facial nerve within the parotid may endanger the nerve during parotid surgeries. The present report is an attempt to help the surgeons to minimize the error that can damage the nerve without previous knowledge of such t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Hence, the cornerstone for a safe and adequate operation is giving emphasis to the exact, detailed description of the anatomy of the facial nerve and its branching pattern. There are several anatomic landmarks for the intraoperative identification of the FN, such as the stylomastoid foramen, the tympanomastoid fissure, the posterior belly of the digastric muscle, the tragal pointer and the retromandibular vein (RMV) [7] , [8] .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the cornerstone for a safe and adequate operation is giving emphasis to the exact, detailed description of the anatomy of the facial nerve and its branching pattern. There are several anatomic landmarks for the intraoperative identification of the FN, such as the stylomastoid foramen, the tympanomastoid fissure, the posterior belly of the digastric muscle, the tragal pointer and the retromandibular vein (RMV) [7] , [8] .…”
Section: Discussionmentioning
confidence: 99%
“… 3 Therefore, understanding surgical landmarks for the facial nerve is essential for safe and effective parotid surgery. 4 The most commonly used surgical landmarks are the stylomastoid foramen, the tympanomastoid suture, the posterior belly of the digastric muscle, the tragal pointer, and the retromandibular vein. 1 , 2 , 4 , 5 Among these landmarks, the retromandibular vein is most commonly used to locate lesions and the facial nerve.…”
Section: Discussionmentioning
confidence: 99%
“… 4 The most commonly used surgical landmarks are the stylomastoid foramen, the tympanomastoid suture, the posterior belly of the digastric muscle, the tragal pointer, and the retromandibular vein. 1 , 2 , 4 , 5 Among these landmarks, the retromandibular vein is most commonly used to locate lesions and the facial nerve. 1 , 5 Several reports have found that the retromandibular vein is medial to the facial nerve in up to 90% of cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations